The biochemistry and physiology of poly-beta-hydroxybutyrate metabolism in methylosinus trichosporium OB3b - Williams, A. M. (Cranfield University, 1988)
The obligate methanotroph, Methylosinus trichosporium 0B3b synthesised up to 20 % of its dry weight as poly-beta-hydroxybutyrate when grown in batch culture or nitrogen limited continuous culture on a methanol/ammonium salts medium. Four soluble enzymes associated with polymer metabolism, D(-)-3-hydroxybutyrate dehydrogenase (3-HBD), acetoacetyl-CoA synthetase, beta-ketothiolase and acetoacetyl-CoA reductase have been purified from the crude extract of this organism. Detailed kinetic studies were conducted on each enzyme and their role in the regulation of polymer metabolism was assessed. Cont/d.